Reseña/Review (Urry, John, "Mobilities", Oxford: Polity Press, ISBN: 9780745634197, 326 págs., 2007) - César Pompeyo (Revista Teknokultura, 2011)
Reseña/Review (Urry, John, "Mobilities", Oxford: Polity Press, ISBN: 9780745634197, 326 págs., 2007)